The awareness level of the doping risks among the participants in fitness centers in Jerusalem Governorate - Shahin, Walid; Yousef , Iyad; Irmaili, Zeyad (Dirasat: Educational Sciences, 2020)
This study aimed to identify the awareness level of the doping risks among the participants in fitness centers in Jerusalem Governorate, and to determine the relationship of age, years of practice, and the goal of practice to the awareness level. The researchers used the descriptive survey approach due to its relevance to the nature of the study. The sample of the study consisted of (118) participants from fitness centers in Jerusalem Governorate, distributed on (3) centers chosen in a simple randomly manner. The researchers used (Petroczi, & Aidman, 2009) measurement tool to verify its authenticity and reliability, and as a tool to collect data that included (22) paragraphs in order to measure the awareness level of the doping risks. The data was analyzed by using the Statistical Package for the Social Sciences (SPSS) program. The results of the study showed that the total degree of awareness of the doping risks among participants in fitness centers in Jerusalem Directorate was medium. It also indicated that there was a level of awareness among participants aged (21-40 years), over 40 years, and those of more than 10 years of experience in sporting activities, towards the risk of doping, the athletes have a higher awareness of the doping risks, than those who participate for health and ideal body building purposes.